2017
DOI: 10.1063/1.5008494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neutron irradiation on the structural and optical properties of PVP/gelatin blends doped with dysprosium (III) chloride

Abstract: Polymer composites of a system of Polyvinylpyrrolidone (PVP)/gelatin/DyCl3·6H2O were prepared in three groups that have different concentrations of PVP/gelatin contents to study the effect of neutron irradiation on their structural and optical properties. Results showed that the interaction of neutrons led to various complex phenomena, mainly bond breaking, main chain scission and intermolecular cross-linking. These processes introduced defects inside the material that were responsible for the changes in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The extent of these changes depends on factors such as radiation type, energy, and flux. In applications like electronics, space research, medicine, dosimeters, and radiometry, specially developed polymers exhibiting specific responses to radiation are essential 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of these changes depends on factors such as radiation type, energy, and flux. In applications like electronics, space research, medicine, dosimeters, and radiometry, specially developed polymers exhibiting specific responses to radiation are essential 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Limin Jiao et al demonstrated that incorporating hexagonal boron nitride (h‐BN) into epoxy resin significantly improves radiation resistance and neutron shielding, a benefit that could extend to other polymer materials as well 23 . Basha further reported that Polyvinylpyrrolidone (PVP) Fourier /gelatin blends doped with dysprosium (III) chloride could serve as good candidate for dosimeters 8 . Moreover, Abuali Galehdari's work indicated an increased elastic modulus in non‐irradiated NCs, suggesting that these materials could be advantageous for neutron shielding structures due to their enhanced mechanical properties 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of different functional groups in gelatine’s structure, such as carboxyl and amino groups, provides gelatine the unique ability to complex with other materials [3] , [4] . To date, scientists have managed to alter many gelatine properties by adding other biomolecules and metal salts for different purposes [5] , [6] . Because of its biocompatibility, non-toxicity and low cost, gelatine has been used in many industries for various applications, including the food, pharmaceutical and medical industries [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%